Kandungan Logam Kadmium (Cd) pada Air Laut, Sedimen, dan Kerang Hijau di Perairan Tambak Lorok dan Perairan Morosari - Ersan Noviansyah; Djamar Tumpal Floranthus Lumban Batu; Isdradjad Setyobudiandi (Jurnal Ilmu Pertanian Indonesia, 2021)
Cadmium metal is dangerous for green mussel organisms because it can interfere with fertility. Green mussels are organisms widely distributed, can survive in poor environments, and sedentary organisms. Green shellfish is a filter feeder and is used as a bioindicator to monitor the concentration of Cd metal in the waters. The research objective was to measure the concentration of Cd metal in sea water, sediment, and green mussel meat in the waters of Tambak Lorok and Morosari. The Cd metal contents of seawater, sediments, and green mussels were measured using Atomic Absorption Spectrophotometer. The results showed that Cd metal concentrations in seawater in May, July, and August 2018 in Tambak Lorok and Morosari waters were below the detection limit (0.001mg/L); 0.002 mg/L; and 0.002 mg/L, respectively. The concentrations of cadmium in sediment in May, July, and August in Tambak Lorok waters were below the detection limit (0.004 mg/kg); 0.0023 mg/kg; and 0.0021 mg/kg, respectively, and in Morosari waters were below the detection limit (0.004 mg/kg); 0.002 mg/kg; and 0.0114 mg/kg, respectively. Cd metal concentrations in green mussel meats in May, July, and August in Tambak Lorok waters were below the detection limit (0.01mg/kg); 0.0060; and 0.1277 mg/kg, respectively, and in Morosari water were below the detection limit (0.01mg/kg); 0.0067 mg/kg; and 0.0493 mg/kg, respectively. Cd metal concentrations in sea water and green mussels in the waters of Tambak Lorok and Morosari were below the quality standard and the concentrations of Cd metal in seawater, sediments, and green mussel meat in the waters of Tambak Lorok and Morosari were not significantly different. Keywords: cadmium, green mussels, morosari, seawater, sediments, Tambak Lorok